Soldering spin-3 opposite helicities in D=2+1 - Dalmazi, D. [UNESP]; Dos Santos, A. L.R.; Mendonça, E. L. [UNESP]; Bittencourt, R. Schimidt [UNESP] (American Physical Society (APS), 2019)
Here we present the soldering of opposite helicity states of a spin-3 particle, in D=2+1, into one parity doublet. The starting points may be either the sixth- or fifth-order (in derivatives) spin-3 self-dual models of opposite helicities. The high number of derivatives avoids the use of auxiliary fields, which has been so far an obstacle for a successful soldering procedure. The resulting doublet model is a new Lagrangian with six orders in derivatives and no auxiliary field. It may be regarded as a spin-3 analogue of the linearized new massive gravity. We check its particle content via a gauge invariant and Lorentz covariant analysis of the analytic structure of the two-point amplitude with the help of spin-3 analogues of the Barnes and Rivers projection operators. The particle content is alternatively confirmed in a specific noncovariant gauge by a decomposition in helicity variables. The soldered model is ghost free and contains two physical states as expected for a parity doublet.